Pelatihan Filmora Dalam Pembuatan Materi Ajar Yang Kreatif Guru Sma Nurul Iman Palembang - Fatmariani; Dilmai Putra; Eka Hartati (Information Technology and Science (ITScience), 2023)
Abstrak: Purpose: From community service to improve learning by utilizing multimedia which is part of technology in the Nurul Iman High School Community, especially teachers and students using Filmora Methodology/approach: The method used in this PKM activity is training and mentoring. Media used by the Filmora application, using Filmora, video editing, using editing tools, creating contemporary templates, color settings, graphics, using formulas and making brochures. This office application application is also used to provide convenience in making learning videos. The service activity method is carried out using teaching media and practice using Filmora multimedia Results/findings: Teachers understand how it works and its benefits, understand the use of the Filmora application, by implementing training and mentoring, understand various types of needs and how it works, get to know the features/menus on Filmora, use Filmora in making teaching materials using multimedia Conclusion: Based on the results of the participant questionnaire graph at an interval of 65-78%, it means that this service activity has a positive impact on increasing the application of science and technology to teachers in improving learning in schools.